BETWEEN SPIRITUAL AUTHORITY AND TEMPORAL POWER: IBN KHALDUN’S VIEWS ON SUFISM - Ahmad, Saiyad Nizamuddin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
In the 9th/15th century the jurist and historian ‘Abd al-Rahman Ibn Khaldun (d. 808/1406) became involved in a dispute that broke out in Andalusia about whether one needed a shaykh to tread the sufi path or whether books sufficed. The dispute was a very heated one and generated much discussion about the nature of sufism and spiritual realization. The response of Ibn Khaldun, as well as the other key figures who issued rulings (fatwas) on this question, are analyzed and Ibn Khaldun’s view is further examined in the light of a much neglected fatwa of his in addition to relevant passages from the Muqaddiama and Shifa’ī -sa’il. It is argued that that Ibn Khaldun favored a sober pursuit of the spiritual path based on rigorous adherence to the Qur’an and Sunna while rejecting the monistic doctrines of Ibn al-‘Arabi and others whom he condemned in the strongest possible terms. Moreover, this condemnation was the result of what Ibn Khaldun perceived to be the dangers inherent in Ibn al-‘ Arabi’s doctrine of the Perfect Man since it allowed for the possibility of individual saintly apotheosis that he further saw as an even more dangerous coinciding of spiritual authority and temporal power.